Vitamin D fortification of dairy products: strategies, technologies, and health impacts - Macarena Ortiz; Andrés Bustamante; Francisco Perez-Bravo; Rodrigo Valenzuela; Catalina Espejo; Lissette Duarte (Revista chilena de nutrición, 2026)
Vitamin D deficiency is a widespread global health concern driven by limited dietary sources, reduced sun exposure, and lifestyle changes. This narrative review synthesizes current evidence on the rationale, technologies, efficacy, and public health implications of vitamin D fortification of dairy products. A literature search was conducted in PubMed, Web of Science, and Scopus for English-language studies, including original research, randomized controlled trials, systematic reviews, meta-analyses, and relevant regulatory or technical documents. The literature examined vitamin D metabolism, the structural properties of dairy matrices that may enhance vitamin D stability and absorption, technological strategies for fortification, global regulatory frameworks, and clinical studies evaluating fortified dairy products. The evidence suggests that the lipid and protein components of milk, yogurt, and cheese can help protect vitamin D from degradation and enhance its bioavailability. Technological advances, including microencapsulation, nanoemulsions, and protein-based delivery systems, may further improve stability during processing and storage. Countries with mandatory fortification policies appear to achieve higher population vitamin D intakes than those relying on voluntary practices. Randomized controlled trials generally show that fortified dairy products can increase serum 25-hydroxyvitamin D concentrations in children, adults, and older populations, although the magnitude of the response varies across studies. Overall, dairy-based vitamin D fortification appears to be a useful strategy to improve vitamin D status, although broader and more coordinated approaches are still needed to address global deficiency.